Use of Corticosteroids in Coronavirus Disease 2019 Pneumonia: A Systematic Review of the Literature - Veronese, Nicola; Demurtas, Jacopo; Yang, Lin; Tonelli, Roberto; Barbagallo, Mario; Lopalco, Pierluigi; Lagolio, Erik; Celotto, Stefano; Pizzol, Damiano; Zou, Liye; Tully, Mark A.; Ilie, Petre Cristian; et al. (Frontiers in Medicine, 2020)
The aim was to investigate the effectiveness of glucocorticoid therapy in patients with COVID-19. A systematic search of the literature across 9 databases was conducted from inception until 15th March 2020, following the PRISMA guidelines. Patients with a validated diagnosis of COVID-19 and using corticosteroids were included, considering all health outcomes. Four studies with 542 Chinese participants were included. Two studies reported negative findings regarding the use of corticosteroids in patients with COVID-19, i.e. corticosteroids had a detrimental impact on clinical outcomes; one study reported no significant association between the use of corticosteroids and clinical outcomes. One study, on the contrary, in 201 participants with different stages of pneumonia due to COVID-19, found that in more severe forms, the administration of methylprednisolone significantly reduced the risk of death by 62%. The literature to date does not fully support the routine use of corticosteroids in COVID-19, but some findings suggest that methylprednisolone could lower mortality rate in more severe forms of the condition.